Separation of Hand Tractor Age Parameter to Analyze Their Effect on Performance Evaluation of Small Scale Mechanization in Madiun using â€Data Envelopment Analysisâ€ - Lutfi, Musthofa (Jurnal Teknologi Pertanian, 2009)
Data Envelopment Analysis (DEA) is a method for evaluating and improving the performance of organizational unit. In this study, DEA applied to evaluate the performances of mechanized small farms in Madiun regency. Firstly, 28 farmers that have been surveyed, were evaluated by combined DEA model which integrated all inputs and outputs sets. Then, two different analyses which had different inputs/outputs set were established; one was cost and revenue analysis and the other was age of hand tractor analysis. Finally, all index of efficiency in combined model and both separated models were compared. The results revealed that 11 farmers judged efficient on combined treatment. However, on comparison of separated and combined treatment appeared that only 2 farmers were truly efficient while 9 farmers were judged partially efficient. Two farmers were truly efficient could be the optimization benchmark in all aspect of farmers performance. Nine partially efficient farms still had a room for improvement performances. Since inefficient farms should be motivated to achieve standard performance much higher on each aspect of performance on separated model, optimization through combined DEA way was better for 17 inefficient farmers.Keywords: data envelopment analysis, separated DEA model, combined DEA model, hand tractor, efficiency of performance, potential improvement